Life of reason : or the phases of human progress - Santayana, George, 1863-1952. (Cambridge Massachusetts : Mit Press, 2014)
Santayana's Life of Reason, published in five books from 1905 to 1906, ranks as one of the greatest works in modern philosophical naturalism. Acknowledging the natural material bases of human life, Santayana traces the development of the human capacity for appreciating and cultivating the ideal. It is a capacity he exhibits as he articulates a continuity running through animal impulse, practical intelligence, and ideal harmony in reason, society, art, religion, and science. The work is an exquisitely rendered vision of human life lived sanely. In this third book, Santayana offers a naturalistic interpretation of religion. He believes that religion is ignoble if regarded as a truthful depiction of real beings and events; but regarded as poetry, it might be the greatest source of wisdom. Santayana analyzes four characteristic religious concerns: piety, spirituality, charity, and immortality. He is at his most profound in his discussion of immortality, arguing for an ideal immortality that does not eradicate the fear of death but offers a way for mortal man to share in immortal things and live in a manner that will bestow on his successors the imprint of his soul. This critical edition, volume VII of The Works of George Santayana, includes notes, textual commentary, lists of variants and emendations, bibliography, and other tools useful to Santayana scholars. The other four books of the volume include Reason in Common Sense, Reason in Society, Reason in Art, and Reason in Science.
Title from PDF title page (viewed on Aug. 19, 2014).
Includes bibliographical references and index.
Keywords: Religion -- Philosophy; RELIGION / Comparative Religion; RELIGION / Essays; RELIGION / Reference; Electronic books